2008
DOI: 10.2169/internalmedicine.47.1565
|View full text |Cite
|
Sign up to set email alerts
|

HHV-8/KSHV-Negative and CD20-Positive Primary Effusion Lymphoma Successfully Treated by Pleural Drainage Followed by Chemotherapy Containing Rituximab

Abstract: The present patient was diagnosed as having human herpes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 9 publications
(1 reference statement)
2
27
0
Order By: Relevance
“…The mean survival time of PEL is approximately 4-6 months; however, in the review of Adiguzel et al [4] of 31 cases of HHV-8-negative effusion lymphoma, the mean survival time was 10.1 months and the mean follow-up period of 13 living patients was 19.5 months [4]. In our two cases, the tumor regressed without any treatment other than drainage of the effusion, and 7 cases of HHV-8-negative effusion lymphoma presenting a similar phenomenon have been reported in the literature [4,5,6,7,8,10]. In 5 cases (including our 2 cases) of these 9 cases, lymphoma cells were involved in the pericardial effusion.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The mean survival time of PEL is approximately 4-6 months; however, in the review of Adiguzel et al [4] of 31 cases of HHV-8-negative effusion lymphoma, the mean survival time was 10.1 months and the mean follow-up period of 13 living patients was 19.5 months [4]. In our two cases, the tumor regressed without any treatment other than drainage of the effusion, and 7 cases of HHV-8-negative effusion lymphoma presenting a similar phenomenon have been reported in the literature [4,5,6,7,8,10]. In 5 cases (including our 2 cases) of these 9 cases, lymphoma cells were involved in the pericardial effusion.…”
Section: Discussionsupporting
confidence: 75%
“…Such cases have been largely reported from Japan and have been designated ‘HHV-8-negative PEL' or ‘PEL-like lymphoma' [2,3,4,5,6,7,8]. However, the clinical and biological characteristics of these tumors differ from those of PEL.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been reported that HHV-8-negative PEL highly expresses B-cell markers, called PEL-like lymphoma [4]. It has also been reported that the malignant cells of HHV-8-unrelated HIV-negative PEL-like lymphoma patients disappear spontaneously without chemotherapy after serous effusion aspiration or drainage [3,[5][6][7][8]. We report two cases of HHV-8-unrelated HIV-negative PEL-like lymphoma in whom no malignant cells were present after effusion drainage alone.…”
Section: Introductionmentioning
confidence: 99%
“…While HHV-8/KSHV positive cases are usually of null phenotype [4,22], HHV-8/KSHV and HIV negative cases highly express B-cell markers [10,11,14,23,24], such as CD19, CD20 and CD79a. In any case, PEL is classified as a mature B-cell neoplasm, based on the presence of immunoglobulin gene rearrangements, and has been suggested to represent the malignant counterpart of a postgerminal center B-cell approaching plasma cell differentiation [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…The median survival is less than 6 months [22], whereas HHV-8/KSHV negative cases may be responsive to rituximab [23,24]. For this reason, and based on the past cardiovascular medical history, an R-COP chemotherapeutic regimen was administered to our patient but no response was achieved up to 3 months after induction, when he was lost to follow-up.…”
Section: Discussionmentioning
confidence: 99%